The impact of conditional cash transfers on children's school achievement : evidence from Colombia (2009)
During the last decade, conditional cash transfer programs have expanded in developing countries as a way to increase school enrollment and deter youth from dropping out of school. However, despite evidence of these programs¿ positive impact on school enrollment and attendance, little is known about their impact on school achievement. Thus, using data from the Colombian conditional cash transfer program Familias en Acción, this study estimated the effect of the conditional subsidy on school achievement. It found that the program does have a positive effect on school achievement for children aged 7 to 12 living in rural areas but practically no effect for the same population living in urban areas. Moreover, the program may actually have a negative effect on the school achievement of adolescents, particularly those living in rural areas. Possible mechanisms of these effects are explored and discussed.